Profitability analysis of a PV micro-installation in a single-family house in Sulejów - Różycka-Wrońska, Ewelina (Instal, 2024)
Photovoltaics remains the clear leader among all renewable energy sources in our country with a 60% share of installed capacity in this sector. The most important criterion for investing in a photovoltaic installation is determining the net profit over the entire life cycle. The article describes an existing PV micro-installation in a single-family house located in Sulejów, designed and installed by a company specializing in this field. The conducted considerations analyzed the production of electricity from PV installations, which is sold in its entirety to the grid at a 20% reduced price per 1 kWh of energy. The calculations assumed a 5% discount rate for the price of 1 kWh of electricity and an increase in demand for electricity of 1% year-on-year. In this paper, the analysis was carried out to check the profitability of the above-mentioned installation and to compare other possibilities of using the financial resources needed for its construction. This analysis includes the investment in long-term funds, the amount allocated for the purchase of PV panels and determines the profit that can be obtained by exploiting PV panels and the money saved thanks to this, to be invested. A safe long-term fund with an average annual return of 7% was adopted for the analysis. Each of the analyzed variants brings financial benefits, but the option that takes into account investing the money saved thanks to the PV installation allows for almost doubling the profit over the life cycle of the micro-installation.